Study of global asymptotic stability in nonlinear neutral dynamic equations on time scales - Ardjouni,Abdelouaheb (Universidad de La Frontera. Departamento de Matemática y Estadística., 2018)
Abstract This paper is mainly concerned the global asymptotic stability of the zero solution of a class of nonlinear neutral dynamic equations in C1 rd. By converting the nonlinear neutral dynamic equation into an equivalent integral equation, our main results are obtained via the Banach contraction mapping principle. The results obtained here extend the work of Yazgan, Tunc and Atan [17].